The Effects of Wavelength and Salinity on Biomass Production from Haematococcus pluvialis (2017)
Currently, microalgae have emerged as promising source of high-value products due to its biomass productivity, high photosynthetic efficiency and non-competitive environment for growth. In this work, biomass production from Haematococcus pluvialis was studied at three salt concentrations (0, 0.45 and 0.9% v/v) and blue, white and red wavelengths in order to evaluate the effects of these factors on microalgae growth. A 32 experimental design was performed and its results were analyzed by Manova test with 95% of reliability. The results obtained suggest that the best combination for biomass production consists of red wavelength and salt concentration of 0% v/v with a maximum productivity of 8172.2 mg/mL.